ANALISIS PENGARUH VOLUME PENJUALAN, HARGA POKOK PENJUALAN DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PERUSAHAAN CV. TERNAK SARI MERTA JAYA TAHUN 2018-2022 - Riani, Ni Made Yunda; Satria, Gde Agung (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the effect of sales volume, cost of goods sold, and operational costson the company's net profit CV Ternak Sari Merta Jaya. This study uses a quantitative approach using asaturated sample technique taken from the company's financial statements of income for 60 months, startingfrom 2018 to 2022. The data analysis technique used is multiple linear regression analysis with the help ofthe SPSS 25.0 program. The results of this study indicate that, the first sales volume has a positive effect onnet income with a value of t (t count) is 2,121 t table, namely 2,003 Both seller's cost of goods have anegative effect on net income with a value of t (t count) is -2,581 > t table namely 2,003 And the threeoperational costs have a negative effect on net profit with a value: t (t count) is -2,526 t table namely 2,003For this reason CV Ternak Sari Merta Jaya Company and similar trading companies must pay attention tosales volume, cost of goods sold , and operational costs in order to get a balanced profit and increase everyyear.